2004
DOI: 10.1089/hum.2004.15.1177
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of Tyrosine Hydroxylase, GTP Cyclohydrolase I, Aromatic Amino Acid Decarboxylase, and Vesicular Monoamine Transporter 2 from a Helper Virus-Free Herpes Simplex Virus Type 1 Vector Supports High-Level, Long-Term Biochemical and Behavioral Correction of a Rat Model of Parkinson's Disease

Abstract: Parkinson's disease is due to the selective loss of nigrostriatal dopaminergic neurons. Consequently, many therapeutic strategies have focused on restoring striatal dopamine levels, including direct gene transfer to striatal cells, using viral vectors that express specific dopamine biosynthetic enzymes. The central hypothesis of this study is that coexpression of four dopamine biosynthetic and transporter genes in striatal neurons can support the efficient production and regulated, vesicular release of dopamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 71 publications
(103 citation statements)
references
References 61 publications
7
95
0
1
Order By: Relevance
“…Several groups have found that ChAT and VAChT genes are adjacent and co-regulated 14 forming a cholinergic genomic locus (see for example [37]). Though we do not now that N18TG-2 cells equip with the VAChT and synaptic vesicles, we cannot exclude the possibility that the transfection with ATP6V0C may induce vesicle formation and transporter expression.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several groups have found that ChAT and VAChT genes are adjacent and co-regulated 14 forming a cholinergic genomic locus (see for example [37]). Though we do not now that N18TG-2 cells equip with the VAChT and synaptic vesicles, we cannot exclude the possibility that the transfection with ATP6V0C may induce vesicle formation and transporter expression.…”
Section: Resultsmentioning
confidence: 99%
“…ATP6V0C plays a central role in H + transport as one part of the multi-subunit complex of ATPase [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. Israel and his group initially proposed that medatophore forms a proteinaceous pore by the six transmemebrane c subunits of ATPase [10,11].…”
Section: Mediatophore As An Ortholog Of Atpasementioning
confidence: 99%
See 1 more Smart Citation
“…An enhancer from the tyrosine hydroxylase promoter (TH) (Ϫ0.5 to Ϫ6.8 kb) was fused to the 5Ј end of the neurofilament heavy gene promoter (NFH) (0.6 kb); and the chicken ␤-globin insulator (INS) (1.2 kb) was fused to the 5Ј end of the TH enhancer (Zhang et al, 2000). This promoter (INS-TH-NFH promoter) supported expression in forebrain neurons for 6 or 14 months, the longest times examined, and time courses in the striatum and the hippocampus documented expression in similar numbers of cells at times approximating the beginning and end of the testing of new object sets (Zhang et al, 2000;Sun et al, 2004) (supplemental Table S1, available at www.jneurosci.org as supplemental material).…”
Section: Methodsmentioning
confidence: 99%
“…Mice with low type 2 VMAT have motor and non-motor manifestations similar to those in PD (45). Moreover, inhibition of vesicular sequestration augments the toxicity of a variety of agents such as 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (46, 47) and 6-hydroxydopamine (48). Conversely, the pesticide and complex I inhibitor rotenone inhibits vesicular uptake (49,50), increases production of DOPAL (51), and evokes apoptosis via oxidation of cytosolic dopamine (52).…”
Section: Figurementioning
confidence: 99%